Adsorption of polyelectrolyte/surfactant mixtures at the air-water interface: modified poly(ethyleneimine) and sodium dodecyl sulfate. - Zhang, X; Taylor, D; Thomas, R; Penfold, J (2011)
The adsorption of surfactant/polyelectrolyte mixtures of sodium dodecyl sulfate (SDS) and different modified poly(ethyleneimine) (PEI) polyelectrolytes at the air-water interface has been studied using neutron reflectivity and surface tension. Modification of the PEI by the addition of short ethylene oxide (EO) or propylene oxide (PO) groups is shown to have an impact upon the surface adsorption behavior. This is due to a modification of the polymer/surfactant interaction, an increase in the intrinsic surface activity of the modified polyelectrolyte, and changes in the relative importance of surface and solution complex formation. For the polyelectrolyte PEI, there is a marked change in the surface adsorption behavior between the addition of a single EO group and that of the (EO)3 group. The addition of a single EO or PO group to the PEI results in an SDS concentration and solution pH adsorption dependence that is broadly similar in behavior to that of the unmodified PEI/SDS mixture. That is, there is strong surface complexation and adsorption down to low SDS concentrations, and there is evidence of a strong interaction at high pH in addition to the strong electrostatic attraction at low pH. The addition of a larger ethylene oxide group, triethylene oxide (EO)3, results in a surface adsorption behavior that more closely resembles that of a neutral polymer/ionic surfactant mixture, similar to that observed for PEI with a larger ethylene oxide group, notably PEI-(EO)7. In that case, the adsorption of the polymer/surfactant complex is much less pronounced. The adsorption arises predominantly from competition between the polymer and surfactant and indicates a decrease in the polymer/surfactant interaction with increasing pH. That is, increasing the size of the ethylene oxide group induces a transition from a strong surface polymer/surfactant interaction to a weak polymer/surfactant interaction.